Wireless intercom and doorbell for a Smart Home / Mohd Norhaslan Alias and Zahari Abu Bakar - Alias, Mohd Norhaslan; Abu Bakar, Zahari (2005)
Smart Home is the terms commonly use to define a residence that uses a Home Controller to integrate the residences various home automation systems. Some of the devices commonly found in Smart Home technology is the “Wireless Intercom” and “Doorbell” design. The Wireless Intercom and Doorbell are functioning to support the home security system. It is easy for the person outside the house to communicate with the person inside the house. In this project, one of the Wireless Intercom and Doorbell has being selected. The wireless intercom has a transmitter and receiver circuit, which is, used modulator and demodulator concept. The doorbell is a wired doorbell that has five melodies that control by the IC M3485, which is the melody IC. The melodies can be changed by pressing the switch at the circuit. Hie Wireless Intercom and Doorbell are connected in order to build a safety system at front gate to the front door at the Smart Home